Minor Antigen Disparities Impede Induction of Long Lasting Chimerism and Tolerance through Bone Marrow Transplantation with Costimulation Blockade - Sinda Bigenzahn; Ines Pree; Christoph Klaus; Nina Pilat; Benedikt Mahr; Elisabeth Schwaiger; Patrick Nierlich; Friedrich Wrba; Thomas Wekerle (Journal of Immunology Research)
Mixed chimerism and tolerance can be successfully induced in rodents through allogeneic bone marrow transplantation (BMT) with costimulation blockade (CB), but varying success rates have been reported with distinct models and protocols. We therefore investigated the impact of minor antigen disparities on the induction of mixed chimerism and tolerance. C57BL/6 (H2b) mice received nonmyeloablative total body irradiation (3 Gy), costimulation blockade (anti-CD40L mAb and CTLA4Ig), and 2×107 bone marrow cells (BMC) from either of three donor strains: Balb/c (H2d) (MHC plus multiple minor histocompatibility antigen (mHAg) mismatched), B10.D2 (H2d) or B10.A (H2a) (both MHC mismatched, but mHAg matched). Macrochimerism was followed over time by flow cytometry and tolerance was tested by skin grafting. 20 of 21 recipients of B10.D2 BMC but only 13 of 18 of Balb/c BMC and 13 of 20 of B10.A BMC developed stable long-term multilineage chimerism (p<0.05 for each donor strain versus B10.D2). Significantly superior donor skin graft survival was observed in successfully established long-term chimeras after mHAg matched BMT compared to mHAg mismatched BMT (p<0.05). Both minor and major antigen disparities pose a substantial barrier for the induction of chimerism while the maintenance of tolerance after nonmyeloablative BMT and costimulation blockade is negatively influenced by minor antigen disparities.